Mesozooplankton biomass and indices of grazing and metabolic activity in Antarctic waters - Hernández-León, S.; Montero, I.; Almeida, C.; Portillo Hahnefeld, A.; Bruce-Lauli, E. (Polar Biology, 2008)
Mesozooplankton distribution and copepod grazing were investigated in the Subtropical Atlantic Ocean near the Azores during the AZORES I (August) and II (April–May) cruises. Mesozooplankton biomass and abundance remained low throughout the region, but significant increases were found related to the presence of the Azores Front. The Azores Front also exhibited maximum values of copepod community ingestion, reaching 250 mg C m–2 ingested daily. This increase in ingestion was related to increases in copepod abundance, but not in copepod gut contents. No relationship was found between gut contents, or ingestion, and phytoplankton biomass or production. Daily cycles were found in copepod gut contents, being higher during the night, but not in copepod abundance. Multi-dimensional scaling analysis revealed differences in copepod taxonomic composition between both sides of the front. During spring, daily copepod ingestion represents an average of 6% of the integrated chlorophyll (Chl) a concentration and 22% of the primary production. These percentages increase to 15% of Chl and 61% of production if we only consider large (>2 μm) phytoplankton. No clear influence of the cyclonic eddy LETICIA was found in mesozooplankton biomass or grazing. A significant effect of the Great Meteor Tablemount was found in copepod abundance and grazing, with higher values located west of the mount. 1382 1373 1,515 Q2 SCIE